Pleadings, Minutes of Public Sittings and Documents / Mémoires, Procès-verbaux des Audiences Publiques et Documents 2024 (International Law E-books Online, Collection 2026., 2025)
This volume contains the texts of written pleadings, minutes of public sittings and other documents from the proceedings in The "Zheng He" Case (Luxembourg v. Mexico), Provisional Measures . The documents are reproduced in their original language. The Tribunal delivered its Order on 27 July 2024. It is published in the ITLOS Reports 2024 . Le présent volume reproduit les pièces de la procédure écrite, les procès-verbaux des audiences publiques et d'autres documents relatifs à la procédure concernant l'Affaire du « Zheng He » (Luxembourg c. Mexique), mesures conservatoires . Les documents sont publiés dans la langue originale utilisée. Le Tribunal a rendu son ordonnance le 27 juillet 2024. L'ordonnance est publiée dans le TIDM Recueil 2024 .